2021
DOI: 10.1021/acs.est.0c02256
|View full text |Cite
|
Sign up to set email alerts
|

Censoring Trace-Level Environmental Data: Statistical Analysis Considerations to Limit Bias

Abstract: Trace-level environmental data typically include values near or below detection and quantitation thresholds where health effects may result from low-concentration exposures to one chemical over time or to multiple chemicals. In a cook stove case study, bias in dibenzo­[a,h]­anthracene concentration means and standard deviations (SDs) was assessed following censoring at thresholds for selected analysis approaches: substituting threshold/2, maximum likelihood estimation, robust regression on order statistics, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…George et al have recently discussed the problem of dealing with data sets which are missing values because some of the measurements are below the detection limit of the analytical method . These are commonly called left-censored data sets, and the problem is what to do with the missing data if one is calculating the central tendency of the data set.…”
mentioning
confidence: 99%
“…George et al have recently discussed the problem of dealing with data sets which are missing values because some of the measurements are below the detection limit of the analytical method . These are commonly called left-censored data sets, and the problem is what to do with the missing data if one is calculating the central tendency of the data set.…”
mentioning
confidence: 99%
“…These data illustrate the need to understand and limit bias introduced by the handling of nondetects, and our work turned to simulation to assess moderately and highly skewed log-normal data that, by design, complemented the case study. Each estimated distribution mean and standard deviation (SD) from our simulation study, shown in Figure 2, represents the average from 1000 data sets with sample size n = 50. The estimates are for uncensored samples and for samples where the lowest 30%, 50%, and 80% of the data was censored.…”
mentioning
confidence: 99%
“…The simulation study is abstract in that its data are not actual analytical measurements, but it has key advantages over a single data set as used in our case study. We noted in the discussion that important distinctions of the simulation study relative to the case study are “(1) the true mean and variance of the underlying population distributions are known, (2) bias estimation based on many samples is, in expectation, more accurate, and (3) the bias estimates are tied only to the distributional characteristics, enhancing generalizability beyond DBA” …”
mentioning
confidence: 99%
See 2 more Smart Citations